A Mixture of Ceramic Biomaterials (Hydroxyapatite and β-Tricalcium Phosphate) and Chitosan as a Scaffold For Critical Sized Defect Bone - Dian Agustin Wahjuningrum; S. Setyabudi; Fery Setiawan; Dwikora Novembri Utomo; Ria Chusnita; Andi Syahrimayani; Arif Rahman Nurdianto (Conservative Dentistry Journal, 2021)
Background: Bone is a living tissue that undergoes a continuous regeneration-remodeling process and the second largest organ implanted after the blood transfusion process. Bones can heal completely, but Critical Size Defects (CSD) require graft materials to support the healing process. There are several graft materials, namely: autologous, allogenous, xenograft, and alloplastic material with their respective advantages and disadvantages through the properties: osteogenesis, osteoconduction, osteoinduction, and others. One of the alloplastic materials is Hydroxypatite/HA and β-Tricalcium Phosphate/β-TCP widely used in the grafting process. HA has the disadvantage of having a low degree of solubility, while β-TCP has a high solubility level when exposed to body fluids. Purpose: To explain the mixture of ceramic biomaterials (Hydroxyapatite and β-Tricalcium Phosphate) and Chitosan as a Scaffold for Critical Sized Defect Bone. Methods: This study used article based review from some journals that contain of the review about HA and -TCP. Results: The CSDs are condition where the bone can not heal by itself. It needs bone graft to bridge the heal of CSDs. One of the transplant materials is ceramic biomaterials contains of HA and β-TCP. Each of material has its strengths and weaknesses so that mixture of these ingredients will increase the positive effects and reduce the negative effects of each ingredient. Conclusion: CSD healing requires a scaffold that mimics cancellous bone in the healing process of bone defects played by the mixture of BCP as a bioceramic material and chitosan as a natural biopolymer with low toxicity and high biocompatibility.